Angola : Request for An Extended Arrangement Under the Extended Fund Facility-Press Release; and Statement by the Executive Director for Angola. (IMF Staff Country Reports; Country Report, 2018)
The Government is implementing a (i) Macroeconomic Stabilization Program, which is focused on strengthening fiscal and debt sustainability; reducing inflation; promoting a more flexible exchange rate regime; improving financial sector stability; and addressing pressures on correspondent banking relationships; and (ii) National Development Plan for 2018-22 to address structural bottlenecks; and promote human development, public sector reform, economic diversification, and inclusive growth. The authorities also focus on improving governance and fighting corruption.